Methylation-sensitive Amplified Polymorphism as a Tool to Analyze Wild Potato Hybrids - Cara, Nicolás (2020)
Methylation-Sensitive Amplification Polymorphism (MSAP) is a versatile marker foranalyzing DNA methylation patterns in non-model species. The implementation of this technique does not require a reference genome and makes it possible to determine the methylation status of hundreds of anonymous loci distributed throughout the genome. In addition, the inheritance of specific methylation patterns can be studied. Here, we present a protocol for analyzing DNA methylationpatterns through MSAP markers in potato interspecific hybrids and their parental genotypes.